Lead (II) adsorption from aqueous solutions onto modified ag nanoparticles: Modeling and optimization. Issue 3 (20th January 2016) - Hosseini, S.J.; Aghaie, H.; Ghaedi, M.; Dashtian, K.; Purkait, M.K.
Abstract : Silver nanoparticles (Ag‐NPs) were synthesized viz. a green method in the presence of trisodium citrate as reducing agent and L‐cysteine as acceptor and capping agent for removal of Pb 2+ ion. Central composite design (CCD) under response surface methodology (RSM) was applied for simultaneous optimization of the importance variables for synthesis of Ag‐NPs and its applicability for Pb 2+ ion removal. The effects of the variables, such as pH, amount of reagent (such as L‐cysteine concentration) and contact time on the Pb 2+ ion removal and subsequent elution steps were efficiently examined. The maximum of Pb 2+ ion removal was obtained while concentration of sodium citrate, silver nitrate, lead nitrate and L‐cysteine was 0.05 M, 0.005 M, 27.78 mg L −1 and 0.25 M, respectively. The optimized resulting of Ag‐NP were applicable for removal of a large content of Pb 2+ ion (105.4 mg g −1 ) from samples with high Pb 2+ ion concentration in short reasonable time. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 743–749, 2016